Comparing the effectiveness of emotion-focused and cognitive-behavioral therapies on body image, anxiety, and depression in women with PCOS - Mansoureh Amirshahi; Ali Akbar Saremi; Reza Nouri; Mohammad Hossein Karbalaee; Robabeh Hosseini Sadat (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a heterogeneous disease that is usually seen in women of reproductive age and causes complications such as body image dissatisfaction, anxiety, and depression. This study was done with the aim of comparing the effectiveness of emotion-focused therapy (EFT) and cognitive-behavioral therapy (CBT) on body image, anxiety, and depression in women with PCOS. MATERIALS AND METHODS: This research was semi-experimental with a pre-test-post-test design with control and follow-up groups. The statistical population included all women with PCOS who were referred to the infertility clinic of Afzalipur Hospital in Kerman in 2022. A total of 45 patients were selected as a sample using the convenience sampling method and then they were randomly assigned to two experimental groups (15 people each) and a control group (15 people). After the pre-test, the experimental groups were subjected to the interventions of EFT and CBT, and afterward the post-test was performed. Cash et al., body image questionnaire, and Beck anxiety and depression questionnaires were used. Data were analyzed using PSS21 software and analysis of variance. RESULTS: The findings revealed that the effectiveness of EFT and CBT on body image, anxiety, and depression is significant (P < 0.05). The comparison of the two therapy showed that the effect of CBT on body image, anxiety, and depression is more than EFT. Moreover, there was no statistically significant difference between the post-test and follow-up scores (P > 0.05). CONCLUSION: According to the results, CBT can reduce dissatisfaction with body image, anxiety, and depression in women with PCOS, therefore it is recommended to use this therapy.